GANJAR PRANOWO'S POLITICAL IMAGE IN ELECTABILITY AS 2024 PRESIDENTIAL CANDIDATE - Riesta Ayu Oktarina; Daniel Andayawan, E Rizky Wulandari, Ratna Puspita Sari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study aims to determine the political image of Ganjar Pranowo in electability as a 2024 presidential candidate. The research observation was conducted on the news of the cancellation of the 2023 u-20 world cup in online media Detik.com, Kompas.com, CNN Indonesia, and Tribunnews. The theory used to examine the theory of political image Soleh Soemirat (2002). The method used in this research is a quantitative method using krippendorff content analysis. Based on the research that has been conducted, the result of this study is that from the four categories stated in Political Image Theory according to Soleh Soemirat, Ganjar Pranowo as a presidential candidate does not fulfill one of the Political Images precisely in the Motivation category. However, Ganjar Pranowo's electability remains good along with Ganjar Pranowo's Political Image which still fulfills the other three categories, namely Perception, Cognition, and Attitude.